Layer-specific Developmental Changes in Excitation and Inhibition in Rat Primary Visual Cortex - Tatti, Roberta (eNeuro, 2017)
Cortical circuits are profoundly shaped by experience during postnatal development. The consequences of altered vision during the critical period for ocular dominance plasticity have been extensively studied in rodent primary visual cortex (V1). However, little is known about how eye opening, a naturally occurring event, influences the maturation of cortical microcircuits. Here we used a combination of slice electrophysiology and immunohistochemistry in rat V1 to ask whether manipulating the time of eye opening for 3 or 7 d affects cortical excitatory and inhibitory synaptic transmission onto excitatory neurons uniformly across layers or induces laminar-specific effects. We report that binocular delayed eye opening for 3 d showed similar reductions of excitatory and inhibitory synaptic transmission in layers 2/3, 4, and 5. Synaptic transmission recovered to age-matched control levels if the delay was prolonged to 7 d, suggesting that these changes were dependent on binocular delay duration. Conversely, laminar-specific and long-lasting effects were observed if eye opening was delayed unilaterally. Our data indicate that pyramidal neurons located in different cortical laminae have distinct sensitivity to altered sensory drive; our data also strongly suggest that experience plays a fundamental role in not only the maturation of synaptic transmission, but also its coordination across cortical layers.